VULNERABILITY PENETRATION TESTING THE COMPUTER AND NETWORK RESOURCES OF WINDOWS BASED OPERATING SYSTEMS: VULNERABILITY PENETRATION TESTING THE COMPUTER AND NETWORK RESOURCES OF WINDOWS BASED OPERATING SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a vulnerability penetration testing for several hosts in WLAN is made. The exploited operating systems were Microsoft Windows 7Enterprise and Microsoft Windows 8. It has been used an exploit named “Java storeImageArray () Invalid Array Index-ing Vulnerability”. Thanks to the open source penetration testing platform - Metasploit Framework the exploit was executed on the target hosts. The most important and critical rea-son the attack being successfully executed is connected with the human factor and interven-tion. Thereby, some security professionals and network administrators can use Metasploit Framework neither to run exploit nor to write security scripts in order to detect and protect the computer and network resources against various malicious cyber-attacks.